Serum Interleukin-6 Expression Level and Its Clinical Significance in Patients with Dermatomyositis - Min Yang; Xiaomin Cen; Qibing Xie; Chuan Zuo; Guixiu Shi; Geng Yin (Clinical and Developmental Immunology)
Objective. To analyze serum interleukin-6 (IL-6) expression level and its clinical significance in patients with dermatomyositis. Methods. Blood samples from 23 adult patients with dermatomyositis (DM), 22 with systemic lupus erythematosus (SLE), 22 with rheumatoid arthritis (RA), 16 with Sjögren's syndrome (SS), and 20 healthy controls were collected. The IL-6 concentration was detected by chemiluminescence immunoassay. Correlations between IL-6 expression levels and clinical features or laboratory findings in patients with DM were investigated. Results. IL-6 expression level of DM patients was significantly higher than that of normal controls, significantly lower than that of RA patients, and slightly lower than that of SLE or SS patients with no significant differences. The incidence of fever was significantly higher in the IL-6 elevated group. Serum ferritin (SF) and C-reactive protein (CRP) were positively correlated with IL-6. Conclusions. IL-6 plays a less important role in DM than in RA. IL-6 monoclonal antibodies may have poor effect in patients with DM.